(untitled) (Research, Society and Development, 2021)
COVID-19 is a worldwide disease. Being an unknown pathology and with great variation. As an infection with a rapid and widespread degree of multiplication and contamination, it forced a world health organization to declare a pandemic state. A disease that can quickly lead to death, especially those with comorbidity, thus began to take extra care with postpartum women, because due to the physiological changes of pregnancy, they tend to evolve into a severe acute respiratory syndrome. Thus, this study aims to analyze the complications generated by the acute respiratory syndrome caused by SARS-CoV-2 for pregnant women and the association between infection and preterm birth. Which presents an integrative review methodology, exploratory and descriptive in nature with a qualitative approach, which was searched in the PubMed and ScinceDirect database platforms, from articles from 2020 and 2021. The association between SARS-coV-2 infection and premature birth, is not yet fully praised, and some authors differ as to opinions and studies. Two important points were discussed, which is the clinical approach through prenatal care in patients affected by COVID-19 and as complications generated by the acute respiratory syndrome caused by SARS-CoV-2 for pregnant women. In this way, it is a theme that presents gaps and unconsolidated answers that lacks studies that encourage this holistic approach.